Accuracy of Genomic Prediction for Milk Production Traits in Philippine Dairy Buffaloes - Herrera, Jesus Rommel V.; Flores, Ester B.; Duijvesteijn, Naomi; Moghaddar, Nasir; van der Werf, Julius H. (Frontiers in Genetics, 2021)
The objective of this study was to compare the accuracies of genomic prediction for milk yield (MY), fat yield (FY) and protein yield (PY) from Philippine dairy buffaloes using Genomic Best Linear Unbiased Prediction (GBLUP) and single-step GBLUP (ssGBLUP) with the accuracies based on pedigree BLUP (pBLUP). To also assess the bias of the prediction, the regression coefficient (slope) of the adjusted phenotypes on the predicted breeding values was also calculated. Two data sets were analysed. The GENO data consisting of all female buffaloes that have both phenotypes and genotypes (n=904 with 1,773 305-day lactation records), was analysed using pBLUP and GBLUP. The ALL data, consisting of the GENO data plus females with phenotypes but are not genotyped (n=1,975 with 3,821 305-day lactation records), was analysed using pBLUP and ssGBLUP. Animals were genotyped with the Affymetrix 90k buffalo genotyping array. After quality control, 60,827 single nucleotide polymorphisms were used for downward analysis. A pedigree file containing 2,642 animals was used for pBLUP and ssGBLUP. Accuracy of prediction was calculated as the correlation between the predicted BVs of the test set and adjusted phenotypes, which were corrected for fixed effects, divided by the square root of the heritability of the trait, corrected for the number of lactations used in the test set. To assess the bias of the prediction, the regression coefficient (slope) of the adjusted phenotypes on the predicted breeding values was also calculated. Results showed that genomic methods (GBLUP and ssGBLUP) provide more accurate predictions compared to pBLUP. Average GBLUP and ssGBLUP accuracies were 0.24 and 0.29, respectively, while average pBLUP accuracies (for GENO and ALL data) were 0.21 and 0.22, respectively. Slopes of the two genomic methods were also closer to one, indicating lesser bias, compared to pBLUP. Average GBLUP and ssGBLUP slopes were 0.89 and 0.84, respectively while average pBLUP (for GENO and ALL data) slopes were 0.80 and 0.54, respectively.